Health-related quality of life and work ability of smallholder rice farm workers in San Jose, Occidental Mindoro, Philippines - Gonzales, Artemio Morado, Jr; Ambong, Ryan Mark Aloro; Bais, Leoniel Salibio; Macaspac, Lendon Perez (UI Scholars Hub, 2020)
Background: Health is an integral form of human capital that can positively influence agricultural worker productivity in the physical, mental, and social domains. Poor health usually represents a burden to farm workers because a failure to meet scheduled tasks on the farm can later affect the dependents who rely on it for food nourishment and sustained livelihood. This study aims to determine the association between health and the work capabilities of smallholder rice farm workers in San Jose, Occidental Mindoro, Philippines. Methods: A cross sectional study was conducted among 100 farm workers. The SF-36 (HRQoL) and Work Ability Index (WAI) questionnaires were used to determine health status and work abilities of the respondents. The association of every health domain was investigated using one-way analysis of variance (ANOVA). Results: The results show that work ability was more associated with physical functioning and vitality scales compared to physical role limitations, bodily pain, general health perceptions, social functioning, emotional role limitations, and mental health in the health dimensions. Conclusion: Given the influence of health-related quality of life, any intervention program for the safeguarding and promotion of work ability among farmers should be based on balancing and optimizing the physical and psychosocial work environments.